The Dialectic of Digital Communication Transformation in Occupational Safety and Health (OSH): Between the Rationality of Technological Efficiency and Workers’ Psychosocial Well-Being - L.M. Zainal Abidin K; Suryo Ediyono (Indonesian Journal of Advanced Research, 2026)
The digital communication revolution has fundamentally transformed the occupational safety and health (OSH) landscape through the adoption of Artificial Intelligence (AI), the Internet of Things (IoT), Virtual Reality (VR), and various digital communication platforms. This study aims to analyze the dialectic between the rationality of technological efficiency and workers’ psychosocial well-being in the context of digital communication transformation in OSH. Using a qualitative approach through a systematic literature review, this study integrates four theoretical frameworks: Diffusion of Innovations (Rogers, 2003), the Technology Acceptance Model (Davis, 1989), the Job Demands–Resources Model (Demerouti et al., 2001), and the Socio-Technical approach (Trist & Emery, 1960). The study’s findings indicate that while digital communication technologies significantly enhance the effectiveness of workplace safety communication, their implementation must take into account workers’ overall psychosocial well-being. From the perspectives of work humanism and the philosophy of technology, the digitalization of occupational safety and health (OSH) should not be solely focused on production efficiency, but rather aimed at creating a balance between technological capabilities and the human dignity of workers. This study recommends the integration of a participatory development communication approach, the application of digital ergonomics principles, and the development of OSH policies that are responsive to the psychosocial dynamics of the digital workplace.